Implants for Cow-Calf and Stocker Beef Cattle - Matt Hersom; Todd Thrift (EDIS)
Getting cattle to put on a lot of muscle quickly is a crucial part of a beef cattle operation’s profitability. Growth promoting implants are one of the most cost-effective ways of increasing lean tissue in cattle and work by releasing hormones into the cow’s body that encourage muscle growth. This 4-page fact sheet explains implants’ mechanisms of action, how implants are administered and used, and concerns associated with implants. Written by Matt Hersom and Todd Thrift, and published by the UF Department of Animal Sciences, August 2015.